QCD axions and axionlike particles in a two-inflation scenario - Hoof, Sebastian; Jaeckel, Joerg (Arxiv, 2017)
We investigate the phenomenology of QCD axions and axionlike particles in a scenario with two eras of inflation. In particular, we describe the possible solutions for the QCD axion field equation after the second inflation and reheating. We calculate the dilution numerically for QCD axions and give an analytic approximation for axionlike particles. While it has been realised before that such a scenario can dilute the axion energy density and open up the parameter space for the axion decay constant
Gesehen am 11.12.2020